Investors' behavior in alternative asset classes - Ellie Papavasiliou; Nikolas Topaloglou; Georgios Tsomidis (SPOUDAI - Journal of Economics and Business, 2022)
We investigate whether alternative asset classes should be included in optimal portfolios of the most prominent investor personae in the Behavioral Finance literature, namely, the Cumulative Prospect Theory, the Markowitz and the Loss Averse types of investors. We develop a stochastic spanning approach for each type of investor. Using the Stochastic Spanning criterion, we construct optimal portfolios with and without alternative assets, namely FX, Commodities, Real Estate and precious metals. Our out of sample comparative performance analysis indicates that investors impression of gains and losses affects significantly the composition and aggregate performance of optimal portfolios and that the alternative asset classes examined are attractive attracted under risk conditions.
Keywords: C12; C13; C15; C44; D81; G11; G14; 330; Parametric and Non-parametric tests; Second Order Stochastic Dominance; Stochastic; Spanning; Cumulative Prospect Theory; Loss Aversion; Markowitz Theory; Probability Weighting